Mindfulness and Burnout: A Correlational Study of Woodball Athletes at the SEA Games 2025 National Training Center - Mariska Dwita Yaumunnishar; Kuston Sultoni; Widy Dewi Nuryanti (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Burnout is one of the psychological problems that athletes often experience due to the high demands of training and competition. This condition can have a negative impact on athletes' performance, motivation, and career sustainability. One of the psychological factors that is suspected to play a role in lowering the risk of burnout is mindfulness, which is the ability of individuals to be consciously and attentively present to current experiences. This study aims to analyze the relationship between mindfulness and burnout in National Training Center SEA Games Indonesia woodball athletes. This study used a cross-sectional correlation design involving 23 woodball athletes who were members of the Indonesian SEA Games National Training Center program. The sampling technique uses total sampling. Mindfulness was measured using the Mindful Attention Awareness Scale (MAAS), while burnout was measured using the Athlete Burnout Questionnaire (ABQ). Data collection was carried out indirectly through filling out an independent questionnaire. Data were analyzed using descriptive statistics and Pearson Correlation tests. The results of the study showed that athletes had a fairly good level of mindfulness and the burnout rate was in the medium category. Correlation analysis showed a significant relationship between mindfulness and burnout (r= -0.516; P<0.05) with strong relationship strength, and of the 3 dimensions of burnout Emotional & Physical Exhaustion most correlated with mindfulness (r= -.608; P<0.01).   These findings indicate that mindfulness is related to burnout conditions in woodball athletes. This study concludes that mindfulness can be one of the psychological factors that play a role in helping athletes manage the stress of training and competition, thus potentially lowering the risk of burnout.